Morphological changes and parasite load of the adrenal from dogs with visceral leishmaniasis - Momo, Claudia [UNESP]; Souza Rocha, Nathalia Alves de [UNESP]; Reina Moreira, Pamela Rodrigues [UNESP]; Munari, Danisio Prado [UNESP]; Mogami Bomfim, Suely Regina [UNESP]; Rozza, Daniela Bernadete [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP] (Brazilian Coll Veterinary Parasitology, 2014)
The objective of this study was to analyze morphological changes and parasite loads in the adrenal gland from 45 dogs with visceral leishmaniasis (VL). The animals were from the Zoonosis Control Center of Aracatuba, state of Sao Paulo, which is an endemic region for the disease. These animals were euthanized due to positive diagnoses of VL. The dogs were classified into asymptomatic, oligosymptomatic and symptomatic groups. The parasite load was determined by immunohistochemistry, using VL-positive dog hyperimmune serum. Nine dogs showed an inflammatory infiltrate composed, predominantly, of plasma cells and macrophages. However, only eight dogs showed macrophages with amastigote forms of the parasite, immunolabeled in the cytoplasm. The medullary and reticular layers were the most affected areas, possibly due to a favorable microenvironment created by hormones in these regions. The density of parasites in the glandular tissue was not associated with clinical signs of VL (P > 0.05). However, the presence of the parasite was always associated with the presence of a granulomatous inflammatory infiltrate. This gland may not be an ideal place for the parasite's multiplication, but the presence of injuries to the glandular tissue could influence the dog's immune system, thus favoring the parasite's survival in the host's different organs.
Keywords: Leishmania infantum chagasi; adrenalitis; Dog; Immunohistochemistry